SOME PROBLEMS CONCERNING THE MULTISTAGE STARTING OF CAGE INDUCTION MOTORS - Göntér, Gábor; Molnár, István (Periodica Polytechnica Mechanical Engineering, 1986)
The transient switching current of three-phase cage motors is the smaller, the smaller is the phase shift between the applied voltage and the voltage induced by the action of the rotor currents in the moment of switch-over. Authors extend the analysis of the star-delta switching– well known from literature - to motors started in four steps and point out the importance of choosing the combination of connections the most advantageous in respect of phase relationships.